Estimation of water pollution and probability of health risk due to imbalanced nutrients in River Ganga, India. Issue 1 (2nd January 2017) - Chaudhary, Mohit; Mishra, Saurabh; Kumar, Arun
ABSTRACT: The River Ganga is the largest, perennial and one of the sacred rivers in India. It supports the lifeline of major population in urban and rural areas existing in the river basin. The river is a chief source of water supply, power generation, river-borne transport and expansion of the urban industrial belt. However, the river receives huge amount of untreated wastewater which imbalances the nutrient concentration at many points along the stretch. Therefore, the present study is focused to estimate the water pollution using water quality indices, such as OPI, national sanitation foundation index (NSFWQI), comprehensive pollution index (CPI) and heavy metal pollution index (HPI), and identify the imbalance nutrients (i.e. NO3, PO4, heavy metals, etc.) in the river. Also, the probability of health risk that might occur by drinking the river water has been classified using risk assessment index (RAI). The water samples were collected in post- and pre-monsoon months in year 2014–2015, from nine sampling locations between Haridwar and Garhmukteshwar. The results indicate that the water quality of River Ganga is unsuitable for drinking during sampling months, because the average NSFWQI was found to be 53.44 and 43.56, while CPI was 2.71 and 2.82 in post- and pre-monsoon, respectively. The river water has been found to be severely contaminated due to heavy metals (i.e. HPI > 3) and indicates the human health risk (i.e. RAI > 1). Therefore, it has been suggested that the river water must be treated to balance the nutrient concentration before used for drinking. Further, by a comparative analysis of indices, NSFWQI and CPI have been found as the better suitable indices to classify the status of water quality.